18.4k views
5 votes
Find the difference of 4.5 x 10 exponent-1 and 2 x 10 exponent -2

User Georgann
by
4.7k points

1 Answer

0 votes

Given expression :


4.5*10^(-1)\text{ \& 2}*10^(-2)

subtract eah other to find the difference,


\begin{gathered} 4.5*10^(-1)-2*10^(-2) \\ \text{Simplify} \\ 4.5*10^(-1)-2*10^(-2)=(4.5)/(10)-(2)/(10^2) \\ 4.5*10^(-1)-2*10^(-2)=0.45-0.02 \\ 4.5*10^(-1)-2*10^(-2)=0.43 \\ 4.5*10^(-1)-2*10^(-2)=(43)/(100) \\ 4.5*10^(-1)-2*10^(-2)=(43)/(10^2) \\ 4.5*10^(-1)-2*10^(-2)=43*10^(-2) \end{gathered}

The difference is 43 × 10 exponent -2

User Johnpaton
by
5.3k points